Correlations between Endothelial Functions and ROS Detection in Diabetic Microvascular Wall: Early and Late Ascorbic Acid Supplementation - Pattarin Sridulyakul; Natchaya Wongeak-in; Suthiluk Patumraj (International Journal of Vascular Medicine)
The correlation between endothelial function and reactive oxygen species detecting from diabetic microvascular wall and the antioxidant effect of ascorbic acid (AA) during early and late phases of diabetic induction were determined. Male Spraque-Dawley rats were divided into four groups: control, diabetes rats (DM, using iv.injection of 55 mg/kg BW streptozotocin, (STZ)), and two groups of DM rats treated with AA (1 g/L, (STZ)) starting on day 2 (DM + AAday2) and week 6th (DM + AA6wk). On 12th week after STZ injection, the findings showed that in DM group, Ach (10−5 M)-induced vasodilatation was decreased, while the number of leukocyte adhesion was increased significantly (𝑃<0.01). Interestingly, these abnormalities induced by DM could be protected or improved in both AA-treated groups, DM + AAday2 and DM + AA6wk. By using dihydrorhodamine 123, our findings also indicated that the existing of ROS productions on diabetic arteriolar and venular walls were different significantly (ROSarteriole = 165.89 ± 24.59 and ROSvenule = 172.26 ± 34.70) (𝑃<0.05). Moreover by using BH4 inhibitor to induce increase in arteriolar ROS, the results also confirmed that AA could improve endothelial function with closed correlation to its potential to reduce vascular ROS content.